Catalytic Hydrothermal Liquefaction of Microalgae using Fe-MCM 41 Catalyst in Presence of Carbon Monoxide - Sharma, R.; Tiwari, A.K.; Singh, A.; Sharma, N. (Asian Journal of Chemistry, 2019)
Among the various types of biomass, microalgae have a potential to become a significant energy source for the production of third generation biofuel. The hydrothermal liquefaction is the direct biomass-to-liquid conversion route carried out in the hot compressed water with or without the presence of a catalyst. In this study, the process pressure and temperature is reduced, but at a lower temperature, bio-oil yield is not high enough to make hydrothermal liquefaction an economical technique. Thus, Fe-MCM 41 catalyst was used to increase the bio-oil yield at low temperatures (250 ºC). This catalyst increased the total bio-oil yield from 42.7 to 61.28 % in hydrothermal liquefaction of Chlorella pyrenoidosa. The bio-oil yield (%) of oil 1, 2 & 3 were 24.72, 17.08 & 19.48, respectively obtained at 250 ºC by using catalyst. Moreover, use of catalyst also resulted in the decrease in oxygen and nitrogen contents of bio-oil and consequently increases in its heating value.